SISTEM HUBUNGAN POMPA SERI DAN PARALEL (System Connecting Series and Parallel pump) - - Senen (Universitas Muhammadiyah Semarang, 2004)
Centrifugal pump is one of kind pump which very much use in the industrial world and houses. The use often used for with special way to increase high pump and capacity pump. With arrange sonne centrifugal pump of akind within connecting series and parallel. The trial made a certain installation of two centrifugal pump connect series and parallel with datas ofthe trial to know head - capacity pump characteristic every type of trial.Keyword : Connecting series and parallel pump